Lifetime HIV testing frequency among women in Sub-Saharan Africa: A DHS-based analysis using zero-inflated negative binomial regression - Agazhe Aemro; Alebachew Ferede Zegeye; Enyew Getaneh Mekonen; Yilkal Abebaw Wassie; Mequannent Sharew Melaku; Basazinew Chekol Demilew (PLoS ONE, 2026)
Background HIV testing is an essential component of HIV prevention and care, yet lifetime testing frequency remains low in sub-Saharan Africa (SSA). This study examines the factors influencing lifetime HIV testing frequency among reproductive-age women in SSA. Methods We analyzed the most recent Demographic and Health Survey (DHS) data from nine sub-Saharan African countries, with an overall weighted sample of 158,722 women aged 15–49. The dependent variable was the lifetime number of HIV tests, and Zero-Inflated Negative Binomial (ZINB) regression was used. Model selection was based on Akaike Information Criterion (AIC) or Bayesian Information Criterion (BIC) and Vuong’s test, favoring the ZINB model over other count models. Adjusted incidence rate ratios (aIRRs) for the count and aOR for the inflation part with 95% confidence intervals (CIs) were reported, with statistical significance set at p < 0.05. Results The mean number of lifetime HIV tests was 2.49 (SD = 7.67), with a median of 0 (IQR = 0–3). Key predictors of lifetime HIV testing included: age (30–39 years: aIRR = 2.94; 40–49 years: aIRR = 3.14), rural residence (aIRR = 1.10), current or former union (aIRR = 1.37 and 1.30, respectively), education (primary: aIRR = 1.19; secondary: aIRR = 1.35; higher: aIRR = 1.81), wealth (richer: aIRR = 1.30; richest: aIRR = 1.34), and employment (manual labor: aIRR = 1.21; skilled work: aIRR = 1.18). Other significant factors included: comprehensive HIV knowledge (aIRR = 1.37), STI awareness (aIRR = 2.21), media exposure (aIRR = 1.25), access to health facilities (aIRR = 1.26), number of sexual partners (1 partner: aIRR = 4.82; 2–3 partners: aIRR = 5.67; 4 or more partners: aIRR = 6.13), early sexual debut (aIRR = 0.61), and region (East Africa: aIRR = 2.82; Southern Africa: aIRR = 7.25). The inflation model showed very low odds of never testing among women with primary and secondary education, lower odds with media exposure (OR=0.40), but higher odds with higher education (OR=5.26) and rural residence (OR=1.93). Conclusions This study indicated that over half of women of reproductive age in SSA have never tested for HIV. Addressing socio-economic, structural, and regional disparities, particularly in West Africa, is crucial, highlighting the need for targeted, equitable, and community-based strategies to expand testing coverage and promote repeat uptake.